The role of global and domestic shocks for inflation dynamics: Evidence from Asia - David Finck; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2019)
This paper studies the determinants of business cycles in small open economies and adds to the discussion about the changing nature of inflation dynamics. We estimate a series of VAR models for a set of six Asian emerging market economies, in which we identify a battery of domestic and global shocks using sign restrictions. We find that global shocks explain large parts of inflation and output dynamics. The global shocks are procyclical with respect to the domestic components of economic activity. We estimate Phillips curve regressions based on alternative decompositions of output into global and domestic components. For the domestic component of GDP we find a positive and significant Phillips curve slope. While the output component driven by oil prices "flattens" the Phillips curve, the component driven by global demand shocks "steepens" the trade-off. Hence, whether or not global shocks flatten the Phillips curve crucially depends on the nature of these global shocks. A series of counterfactuals supports these findings and suggests that the role of monetary policy and exchange rate shocks is limited.
Keywords: E3; E5; F4; 330; inflation targeting; business cycle; open economy; monetary policy; Phillips curve